CONTEMPORARY METHODS OF TEACHING LANGUAGES - Matershova, A.I.; Pugacheva, A.V. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
This article describes the features of thelanguage teaching contemporary methods. The goal of this article is to analyze theoretical aspects of the contemporary methods and to identify the features of practical implementation, their advantages and disadvantages. Much attention is given to communicative, conscious and intensive methods. This article describes principles of communicative, conscious, audio-lingual and audiovisual methods. The text gives valuable information about the specific features of the development of learners’ communicative competence.
Keywords: teaching methodology; language; communicative method; communicative competence; interactivity